A New Procedure Assisted by Digital Techniques for Secondary Mandibular Reconstruction With Free Fibula Flap. Issue 8 (November 2016) - Yu, Yao; Zhang, Wen-Bo; Liu, Xiao-Jing; Guo, Chuan-Bin; Yu, Guang-Yan; Peng, Xin
Abstract : Purpose: To describe a new procedure assisted by digital techniques for secondary mandibular reconstruction with free fibula flap. Methods: The 3-dimensional (3D) reconstruction images for vessels were used to demonstrate the vascular diameter and location, which help select the most suitable vein and artery for anastomosis. Maxillary and mandibular stone models of the patient were fabricated and a stable occlusal relationship was determined on an articulator. The 3D tooth model data were scanned using a 3D-optical measuring system, and the obtained stereolithographic (STL) data were imported to Geomagic software. Preoperative maxillofacial and fibular noncontrast-enhanced computed tomography scans were acquired, and the data were imported to ProPlan CMF software. The maxilla and mandible were segmented, and STL data were imported to Geomagic software. The registration function was used to determine the ideal mandibular position. First, with the maxillary position fixed, the maxillary and mandibular models were registered with the maxilla. Then, with the tooth model positions fixed, the mandible was registered with the models. The STL data for the mandible were imported to ProPlan CMF software. Virtual plan and surgical navigation were used to design and correct the mandibular and fibular position. Results: Our technique enabled precise recovery of the original mandibular configuration in this patient. The shift in the reconstructed mandible and fibular segment was <5 mm. Conclusions: The authors described a new procedure for secondary mandibular reconstruction with a free fibular flap using digital techniques involving surgical navigation, which have the potential to improve the clinical outcomes of this procedure.